CONSTITUTION OF CIVIL SOCIETY: FROM THE THEORY TO PRACTICE - Dmitry A. Smirnov; Konstantin A. Strus (Вестник Северо-Кавказского федерального университета, 2022)
Need of development and adoption of the constitution of civil society locates in article. It is analyzed the main ideas of civil society. The author's structure of the fundamental law of civil society is offered.